ANALISIS KINERJA ORGANISASI PADA BADAN KEPEGAWAIAN DAERAH DI KABUPATEN KENDAL - Fitriana, Nona; Hariani, Dyah; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2015)
The analysis of oranization performance of Local Staffing Agency of Distric of Kendal is effected by an existence of the lack of discipline around there. For example there is a employee who come late to office and sometime there are also some employees who do not stay in their room during working hours. This research uses qualitatif method that means all the data are explained by description. The place of research is in Local Staffing Agency of Distric of Kendal. The data is gathered from doing some interviewes. The primary data gathers from some informants. Another data are gathered from some documentations. The choosing of informant is done by using purposive sampling. To ensure the quality of data the researcher uses triangulation technique. Based on Dwiyanto (2002) there are five phenomenons that affect the organization performance, that are productivity, the quality of service, responsivity, responsibility and acuntability. Whereas there are two factors that affect the organization performance of Local Staffing Agency of District of Kendal that are human resourches factor and facility and also infrastructur factor. The performance of organization of Local Staffing Agency of Distric of Kendal basically is good, but there are some things that need to be grown up. The factors that affect the performance are; there are some employees who are lazy and there are also some employees who do not fluent yet in using the computer. The recomendation that given by writer are (1) all of employees have to keep the teamwork; (2) all of employees have to increase the dicipline toward working hors; (3) the leader of local staffing agency have to minimalize in giving the task suddenly; (4) the local staffing agency of district kendal have to give the employee a computer training; (5) the employee have to keep the motivation in working.